The ESCRT‐III complex contributes to macromitophagy in yeast. (16th June 2021) - Wu, Zulin; Xu, Haiqian; Liu, Junze; Zhou, Fan; Liang, Yongheng
Abstract: Mitochondria play important roles in energy generation and homeostasis maintenance in eukaryotic cells. The damaged or superfluous mitochondria can be nonselectively or selectively removed through the autophagy/lysosome pathway, which was referred as mitophagy. According to the molecular machinery for degrading mitochondria, the selectively removed mitochondria can occur through macromitophagy or micromitophagy. In this study, we show that the endosomal sorting complex required for transport III (ESCRT‐III) in budding yeast regulates macromitophagy induced by nitrogen starvation, but not by the post‐logarithmic phase growth in lactate medium by monitoring a mitochondrial marker, Om45. Firstly, loss of ESCRT‐III subunit Snf7 or Vps4‐Vta1 complex subunit Vps4, two representative subunits of the ESCRT complex, suppresses the delivery and degradation of Om45‐GFP to vacuoles. Secondly, we show that the mitochondrial marker Om45 and mitophagy receptor Atg32 accumulate on autophagosomes marked with Atg8 (mitophagosomes, MPs) in ESCRT mutants. Moreover, the protease‐protection assay indicates that Snf7 and Vps4 are involved in MP closure. Finally, Snf7 interacts with Atg11, which was detected by two ways, glutathione‐S‐transferase (GST) pulldown and bimolecular fluorescence complementation (BiFC) assay, and this BiFC interaction happens on mitochondrial reticulum. Therefore, we proposed that the ESCRT‐III machinery mediates nitrogen starvation‐induced macromitophagy by the interaction between Snf7 and Atg11 so that Snf7 is recruited to Atg32‐marked MPs by the known Atg11–Atg32 interaction to seal them. These results reveal that the ESCRT‐III complex plays a new role in yeast on macromitophagy. Abstract : Autophagy in yeast can be divided into nonselective and selective autophagy, each of which can be further divided into macroautophagy and microautophagy. The ESCRT complex plays a vital role in membrane repair, vesicle trafficking and autophagy, including nonselective macroautophagy and microautophagy. In this study, we found that the ESCRT‐III complex is involved in selective degradation of mitochondria by macroautophagy (macromitophagy) under nitrogen starvation in yeast. Meanwhile, the mitochondrial marker Om45 and the mitophagy receptor Atg32 accumulate on autophagosomes (mitophagosomes), which are open in ESCRT mutants snf7 ∆ and vps4 ∆. Furthermore, Snf7 interacts with a selective autophagy adaptor Atg11, which interacts with Atg32 on mitochondrial reticulum. We proposed that the ESCRT‐III machinery mediates nitrogen starvation‐induced selective macromitophagy by using Atg11 to bridge Snf7 and Atg32 to seal Atg32‐marked mitophagosomes by ESCRT‐III with Snf7.